(untitled) (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2024)
It is a widely held age old belief that attendance system plays a vital role in an organization as it defines its employee productivity. On the other hand the changing business landscape is posing multiple challenges to the modern day managers to confront. In order to boldly face the challenges and attain competitive edge many companies are on an innovation spree and hence challenging the stereotypes. The present case is related to a more than six decade old textile company’s HR head’s dilemma of whether to continue its struggle for a better attendance management system? or doing away with it, as has been done by a few other companies. Exhibits help corroborate and supplement the information presented in the case. End of the case poses certain questions, answers of which can be discussed in the classroom with the help of teaching notes.